2016
DOI: 10.4103/0301-4738.191497
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of glaucoma in Eastern India: The Hooghly River Glaucoma Study

Abstract: Context:Glaucoma is the leading cause of global irreversible blindness. No recent study with adequate sample size has been carried out to estimate glaucoma prevalence in Eastern India.Aims:The aim of this study was to assess and compare the prevalence and types of glaucoma in a rural and urban East Indian population.Settings and Design:The Hooghly River Glaucoma Study (HRGS) is a population-based cross-sectional study from West Bengal. A tertiary hospital in Kolkata was our urban study center. Our rural study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
33
2
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 21 publications
3
33
2
2
Order By: Relevance
“…Among the 750 patients, 93 (12.4%) had glaucoma, which is high compared to other studies done in general population 2,6 (Table 4) (Figure 4). In our study, glaucoma was significantly more in diabetic patients with HT53 (15.2%) than patients without HT40 (10.0%) p value significant at 0.05 level (Table 5) ( Figure 5).…”
Section: Resultsmentioning
confidence: 70%
“…Among the 750 patients, 93 (12.4%) had glaucoma, which is high compared to other studies done in general population 2,6 (Table 4) (Figure 4). In our study, glaucoma was significantly more in diabetic patients with HT53 (15.2%) than patients without HT40 (10.0%) p value significant at 0.05 level (Table 5) ( Figure 5).…”
Section: Resultsmentioning
confidence: 70%
“…The methodology of HRGS has been discussed in details elsewhere. [ 1 ] This cross-sectional study was approved by the Institutional Ethics Committee and adheres to the tenets of the Declaration of Helsinki. Kolkata city, our urban study area, is divided into 15 boroughs and 141 wards.…”
Section: Methodsmentioning
confidence: 99%
“…Glaucoma is the leading cause of global irreversible blindness[ 1 ] and an important public health issue. [ 2 ] Population-based studies are important for assessment of disease burden, health-care policy planning, and appropriate resource allocation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…13 Till now seven population based studies have been reported in India, out of which three are from Tamil Nadu, one from Andhra Pradesh, two from Bengal and one from Amritsar (Punjab). [13][14][15][16][17][18][19][20] All the seven studies have variation in prevalence data; it is because they have used different diagnostic criteria. There is a lack of data in Punjab and only one study so far is published.…”
Section: Introductionmentioning
confidence: 99%